Antibacterial Activity of Miana Leaf Ethanol Extract (Coleus scutellarioides (L) Against Some Pathogenic Bacteria Using The TLC Method - Bioautography - Fitriana, Fitriana; Harmunanto, Kartika Hatari; Zulkarnain, Iskandar (Journal Microbiology Science, 2024)
Miana (Coleus scutellarioides (L.). is one of the plants that grows in areas with rather moist or slightly watery soil conditions, this plant is often consumed by people in Indonesia and is believed to be a medicinal plant. Empirically, miana leaves are used as antibiotics because they are known to have antibacterial activity. The purpose of this study was to determine the bioautogram profile of miana leaf ethanol extract against several pathogenic bacteria using the TLC-Bioautography method. As for the results of this study, ethanol extract of miana leaves (Coleus scutellarioides (L.)) has the potential as antibacterial against bacteria Staphylococcus aureus, Escherichia, Pseudomonas aeurigosa, and Streptococcus mutans, where for Staphylococcus aureus bacteria there are 2 active spots with Rf values of 0, 98, 0.32 and Streptococcus mutans bacteria there are 3 active spots with Rf values of 0.98, 0.76, and 0.69 respectively. As for Escherichia bacteria, there is 1 active spot with an Rf value of 0.81 and Pseudomonas aeurigosa bacteria there are 3 active spots, namely 0.87, 0.49, and 0.29, respectively.